Blending of bambangan kernel fat-stearin, palm oil mid-fraction and palm stearin to formulate cocoa butter equivalent - Norazlina Mohammad Ridhwan (2023)
Pure vegetable fats and oils often had unsatisfactory properties in speciality fat applications such as cocoa butter equivalent (CBE). There have been substantial studies showing that fat modification using fractionation and blending improves the properties of the pure fats and yields a product with desirable properties. Therefore, this study aimed to determine the effects of blending fractionated bambangan kernel fat-stearin (BKF-SS) with palm oil mid-fraction (POMF) and palm stearin (PS) in CBE formulations on their physicochemical, thermal, morphological properties and their compatibility with cocoa butter (CB). The results showed that all blends at five varying ratios (90:10, 85:15, 80:20, 75:25, and 70:30 %) have similar physicochemical properties with CB. Nevertheless, only the blend containing 70% BKF-SS and 30 % POMF (PMF5) and PS (PS5) showed a remarkable resemblance to CB’s composition. Both PMF5 and PS5 mimic the fatty acids of CB with 18.87 – 21.73 % palmitic, 38.23 – 38.92 % stearic, and 31.12 – 34.05 % oleic acid with improved thermostabilities (high solid fat content (SFC) at 30 ºC but reached to 0 % at 40 ºC). The fatty acids and TAG composition of the blends were significantly different (P<0.05) compared to the individual BKF-SS, wherein BKF-SS, the stearic acid, and 1,3-distearate-2-oleate-glycerol (SOS) content were higher. The changes in the composition could be attributed to high palmitic acid and 1,3-dipalmitate-2-oleate-glycerol (POP) content in the palm fractions that reduced the stearic composition. In addition, it showed low rancidity values, which indicates these blends are stable and have better quality. The results also featured similar melting and crystallisation profiles. They exhibited β and β’ polymorphic forms, which correspond to a mixture of disc-shaped crystals with a needle-like crystal structure of 40 – 50 μm diameter. These morphological features indicated similar textural attributes to CB; hence, they were analysed for compatibility with CB. Although the 1-palmitate-2-oleate-2-stearate (POS) content in the blends is slightly lower, PMF5 and PS5 have comparable POP (10.35 -12.07 %) and SOS (29.57 – 30.22 %) content with CB. The TAG profiles, SFC, morphology features and straight line on the iso-solid diagram indicates that the BKF-SS blended with POMF and PS has better compatibility with CB than the individual BKF-SS. The results obtained in this study proposed that BKF-SS integrated with palm fractions, especially POMF at 70:30 % ratio (PMF5), showed better resemblances properties and showed potential application as CBE. In conclusion, this palm fraction successfully improves the composition, thermal and morphological properties of BKF-SS and increases the compatibility of the fractionated BKF-SS with CB.